A quality assessment of public water fountains and relation to human health: a case study from Yozgat, Turkey. (12th October 2018) - Birgin Iritas, Servet; Ali Turksoy, Vugar; Deniz, Serdar; Kocoglu, Serhat; Kirat, Gullu; Can Demirkesen, Ali; Baba, Alper
Abstract: Public fountains are very common and everyday people appreciate the benefits a water fountain can bring. However, consumption of public fountain water in some country has decreased because of growing concerns that constituents in fountain water may have adverse effects on health. A few studies have examined the safety of public fountains, proposing only limited evidence of fountain‐related health issues in Turkey. Most of these public fountains are sourced from natural springs in Turkey. In this study, a 177 fountain water and 32 rock samples were analysed for source and quality of water. The geology of the region has the direct impact on the quality of the public fountain water. The results indicate that the level of some elements exceeded the limit values determined by WHO and US.EPA. The most striking high values were observed for iron (Fe), nickel (Ni), aluminum (Al), arsenic (As) and bromine (Br) concentrations.